2011
DOI: 10.1111/j.1540-8159.2011.03071.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Complex Fractionated Electrograms Recorded During Atrial Fibrillation in a Canine Model

Abstract: In this pacing-induced AF model, common causes of CFEs include: (1) wavefront collision, (2) conduction through channels of functional block, (3) reentry. The vast majority of these CFE regions were caused by wavefront collision rather than true "drivers" of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…These results indicate that CFAEs are strongly influenced by the spatial resolution because CFAEs reflect not only localized reentry or AF drivers but also wavefront collisions, conduction through channels of functional block, and pivot points [14]. Furthermore, the majority of the CFAEs have been demonstrated to reflect far-field potentials which are often prevalent at anatomic junctures such as the coronary sinus or septum [15].…”
Section: Discussionmentioning
confidence: 96%
“…These results indicate that CFAEs are strongly influenced by the spatial resolution because CFAEs reflect not only localized reentry or AF drivers but also wavefront collisions, conduction through channels of functional block, and pivot points [14]. Furthermore, the majority of the CFAEs have been demonstrated to reflect far-field potentials which are often prevalent at anatomic junctures such as the coronary sinus or septum [15].…”
Section: Discussionmentioning
confidence: 96%
“…Recently, CFAEs have been thought to represent localized reentry, AF drivers, wavefront collision, and conduction through channels of functional block and pivot points. 7 In contrast, high DF sites indicate local synchronous high-frequency activations that are likely to be closely linked to localized reentry or the AF driver(s). 8 Detailed analysis of the NavX-based DF and CFAE maps showed that most CFAE activity occurred near a high DF site and that the cores of the widely distributed continuous CFAEs sites correlated with the high DF sites.…”
Section: Presence Of Eat and Its Influence On Afmentioning
confidence: 99%
“…[23][24][25] However, the lack of consistency between models and in particular in human studies leads ultimately to a fundamental concern for which the question of fibrosis acts as an ideal example: If fibrillation of animal atria can be provoked ubiquitously and variably, how can all such models be representative of human AF and how can we discover in which respects any of them are representative?…”
Section: Fibrosismentioning
confidence: 99%